Physicochemical and microbiological characteristics of the Paipa cheese whey (2018)
Paipa cheese is the only ripened cheese in Colombia. The whey of Paipa cheese can be considered an environmental problem; therefore, its characterization may contribute to propose options for its industrialization, and to guarantee that the whey is discarded in proper manners. The physicochemical and microbiological characteristics of samples of whey from three representative plants of Paipa cheese were analyzed. The averages evaluated showed significant statistical differences (P≤0,01) in the following parameters: calories, carbohydrates, humidity, fat, protein, mesophilic aerobes, molds, lactic acid bacteria (BAL), and yeast. The average results of the analyzed samples had values within the classification range of sweet whey, with an average pH of 5,7 and lactose of 5,1%; however, they lacked good sanitary quality. The benefits of the whey composition, particularly in regards to the averages in protein (0,71 ± 0,12), ashes (0,42) and fat (0,5 ± 0,14), and its counts in yeast (38 x 102 on average) and BAL (10,7 x 104 on average) position the Paipa cheese whey as an alternative as a culture medium and raw material for biotechnological processes in the production of different products in the food industry.